KOMITMEN UNI EROPA DALAM PEMENUHAN PRINSIP NON-REFOULEMENT TERHADAP NEGARA-NEGARA ANGGOTA (Studi Kasus Krisis Pengungsi di Yunani Pascakebakaran Kamp Moria) - Sharleen Dessyhana Chrisella (Faculty of Law Universitas Sebelas Maret, 2022)
One of the countries in Europe with the biggest refugee crisis is Greece and triggers the emergence of refoulement. The non-refoulement principle is an absolute form protection for a refugee and must be obeyed by all ratifying countries. On that basis, Greece needs an additional assistance from the European Union as a regional organization that houses most European countries. This study aims to explain the commitment of the European Union in fulfilling the principle of non-refoulement to the refugee crisis in Greece, especially after the fire incident at Camp Moria. This research is a normative legal research with a statute approach and a conceptual approach. The sources of legal materials used are based on 1951 Convention on the Status of Refugees also the non-refoulement principle. The technique of collecting legal materials used is library research and analyzed through inductive analysis techniques. The results showed that the condition of the refugee crisis in Greece especially after the fire at Camp Moria was so alarming where the refugees are in danger of being refoulemented. In dealing with the refugee crisis that occurred in Greece, the European Union has tried to issue policies and decisions but the policies have not been implemented optimally.